30 YEARS AFTER THE CREATION OF THE METROPOLITAN INSTITUTE FOR PLANNING OF THE MUNICIPALITY OF LIMA, PERU, 1991-2021 - Castillo-García, Rodolfo Francisco (2020)
The objective of this article is to make a chronicle of the history and the future of the Metropolitan Planning Institute (IMP), of the Metropolitan Municipality of Lima (MML), as a permanent organism for planning the local, urban and territorial development of the Province of Lima, since its created in 1991, thanks to the management of young technicians; until 2021, when 30 years have passed since its creation, and when it would have to face the challenge of formulating a new Sustainable Urban Development Plan for the Lima Callao Megalopolis with Vision to 2050. This should be the propitious occasion for the relaunching of the institutional image and the role of the IMP in the conduct, orientation, and regulation of the planning of sustainable urban development of the Lima Callao Megalopolis with a view to the twelfth anniversary of the independence of Peru, to the fi ftieth anniversary of the Spanish foundation of Lima, and the second fi ftieth anniversary of the 21st Century. Keywords: Lima and Callao megalopolis – metropolitan planning institute – sustainable urban development